Modeling and Simulation of Minimarket Cashier Queues to Reduce Customer Waiting Time at Indomaret Tuntungan I - M. Fadly Rizky Pratama; Fahmi Nur Alimsyah Purba; Alief Emir Hakim Irwansyah; Khairun Akbar Ramadhan; Dyah Puspita Anggraini; Retno Setyaningsih (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Customer satisfaction in the modern retail industry is significantly influenced by the efficiency of cashier services. Long waiting times can lead to dissatisfaction and potential customer loss. This research aims to analyze and optimize the cashier queuing system at Indomaret Tuntungan I using a discrete event modeling and simulation approach. Primary data on customer arrival intervals and service times were collected through direct observation. A simulation model was constructed using Arena software to replicate the existing system, which operates with two cashiers and separate queues. Several optimization scenarios were proposed and tested, including adding cashiers and implementing an integrated single queue system. The key performance metrics measured were average customer waiting time, queue length, and cashier utilization. The simulation results demonstrate that the combined scenario, featuring a single queue with one additional cashier activated during peak hours, yielded the most significant improvement. This configuration successfully reduced the average waiting time by 67.4% to 2.55 minutes, decreased the maximum queue length to 2.8 people, and achieved a balanced cashier utilization rate of 68.7%. The findings provide a data-driven recommendation for minimarket management to enhance service speed through a synergistic approach of queue restructuring and dynamic resource allocation..